1998
DOI: 10.1023/a:1007721917561
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Carnitine is an important cofactor in the intermediary metabolism of the heart, and carnitine deficiency is associated with congestive heart failure. We therefore studied the effects of acute (IV bolus, 30 mg/kg body weight) and chronic administration (1.5 mg/d for 1 month) of propionyl-L-carnitine on hemodynamics, hormone levels, ventricular function, exercise capacity, and peak oxygen consumption in 30 patients with chronic congestive heart failure (NYHA II-III, mean EF 29.5 +/- 7%) in a phase II, parallel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Improvement in echocardiographic parameters similar to our findings has been documented which validates our data [28]. The effect of L -carnitine treatment on ejection fraction has been inconsistent [28,29]. However, these studies lack a control group in contrast to our study showing a positive effect of L -carnitine treatment in comparison to a control group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Improvement in echocardiographic parameters similar to our findings has been documented which validates our data [28]. The effect of L -carnitine treatment on ejection fraction has been inconsistent [28,29]. However, these studies lack a control group in contrast to our study showing a positive effect of L -carnitine treatment in comparison to a control group.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of L -carnitine treatment in patients with heart failure has shown significant increases in exercise capacity, maximum exercise time, peak heart rate, and peak oxygen consumption consistent with a positive effect of L -carnitine treatment as was found in our population after L -carnitine treatment [28,29,30]. Improvement in echocardiographic parameters similar to our findings has been documented which validates our data [28]. The effect of L -carnitine treatment on ejection fraction has been inconsistent [28,29].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Subsequently, several studies have shown that supplementation of a single AA in patients with HF was able to improve the functional capacity. Mancini et al17 observed in 60 patients affected by stable chronic HF that the supplementation of L-carnitine for six months improved the maximum exercise duration, and Anand et al18 described 30 patients with HF in whom the supplementation of L-carnitine for one month improved peak VO 2 and exercise duration. The major limitation of these early studies is the supplementation of a single type of AA.…”
Section: Discussionmentioning
confidence: 99%